ТАКСОНОМИЧЕСКИЙ АНАЛИЗ ЖУЖЕЛИЦЫ (COLEOPTERA, CARABIDAE) УЗБЕКИСТАНА (Scientific journal of the Fergana State University, 2024)
Ground beetles are essentially soil insects that are widespread in all regions of Uzbekistan; a total of 454 species and subspecies have been recorded, ground beetles belonging to 12 subfamilies, 88 genera and subspecies. This list of weevils has been compiled for the first time in Uzbekistan, and this discovery is of great scientific and practical importance in studying the fauna and distribution of these beetles, and at the same time in determining effective measures to combat pest species.